The effect of land use and pedestrian infrastructures design on pedestrian-based transit ridership (PBTR) at urban rail transit station. A case study in Kuala Lumpur, Malaysia - Jaafar Sidek, Mohd Farid; Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (Eastern Asia Society for Transportation Studies (EASTS), 2017)
PEMANDU, a governemnt secretariat involves in improving public transit has recorded 80.4% private trip are made dailly in Kuala Lumpur as end of 2015. It creates congestion on the road especially during morning and evening peak hours. Government has spent billions of ringgit in providing road-based infrastructures in order to overcome high travel demand. Apparently, travel demand is keep increasing year by year. Thus, transit ridership is one of viable solutions in addressing the tremendous increase in travel demand particularly in urban areas. However, public transit usage is not encouraging in major car-oriented cities in Malaysia including Kuala Lumpur. Ampang line urban rail transit is one of two Light Rail Transit (LRT) available providing services to Greater Kuala Lumpur (GKL) dwellers. Sentul, Pandan Jaya, and Bukit Jalil are three of 25 transit stations available along the line as at end of 2015. These urban rail transit stations experiencing imbalance proportion of ridership which lead to economic loss and supress the optimum use of transit line. Therefore, increasing urban rail transit ridership at transit stations are important to avoid economic loss and optimizing uses of transit line. Literature shows that PBTR at transit station can be increased by land use planning and provision of pedestrian infrastructures design surrounding transit station. Thus, this paper is to study to the effect of land use and pedestrian infrastrucutres design on PBTR at transit station at urban rail transit station by selecting Kuala Lumpur, Malaysia as a case study.